Enhanced magnetic properties in Nd-Fe-B magnets prepared by spark plasma sintering via die-upsetting process - 胡志华 储林华 李军 刘颖 (Journal of rare earths, 2011)
The magnetic properties and microstructure of Nd-Fe-B magnets prepared by spark plasma sintering with different die-upsetting processes were investigated. The results showed that the optimum magnetic properties of die-upset Nd-Fe-B magnets were obtained at 680 ℃ when the die-upset level was 60%, and the degree of magnetic alignment was 0.84. The microstructures showed that the coarse grains oc-curred predominantly within certain areas, and abnormal grain growth was not observed within the major areas of well-aligned grains. There existed many small spherical grains, which stacked together and were not aligned during die upsetting when the deformation temperature was 650 ℃. These small spherical grains grew up, and were aligned when the deformation temperature increased from 650 to 680 ℃, which could improve the crystallographic alignment of die-upset Nd-Fe-B magnets.